Organization of experimental study on forming a health culture of future doctors by means of health-supporting technologies - Nazaruk, Victor (Journal of Education, Health and Sport, 2015)
Nazaruk Victor. Organization of experimental study on forming a health culture of future doctors by means of health-supporting technologies. Journal of Education, Health and Sport. 2015;5(1):241-248. ISSN 2391-8306. DOI: 10.5281/zenodo.16915 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A241-248 https://pbn.nauka.gov.pl/works/555197 http://dx.doi.org/10.5281/zenodo.16915 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. Organization of experimental study on forming a health culture of future doctors by means of health-supporting technologies Victor Nazaruk Ternopil State Medical University by I.Ya. Horbachevsky Summary The article describes the progress of the experimental study of a health culture formation in future doctors by means of health promotion technologies. We have shown the positive impact of integrative links between the disciplines "Human Anatomy" and "Physical Education" in the example of studying the human skeleton and positive impact of exercises on its formation and functioning. It is expected that the proposed organization of experimental study will contribute to improvement a health culture in the future physicians. Keywords: health culture, future doctors, health-supporting technologies, organization of experimental.